Vertex Equitable Labeling of Cyclic Snakes and Bistar Graphs (Journal of Scientific Research, 2013)
Let G be a graph with p vertices and q edges and let A = {0, 1, 2,..., }. A vertex labeling f: V (G) ® A induces an edge labeling f * defined by f *(uv) = f(u) + f(v) for all edges uv. For , let vf (a) be the number of vertices v with f(v) = a. A graph G is said to be vertex equitable if there exists a vertex labeling f such that for all a and b in A, and the induced edge labels are 1, 2, 3,, q. In this paper, we establish vertex equitable labeling of square graph of and splitting graph of and kC4 snake(k?1) and the generalized kCn snake is vertex equitable if nº0(mod4),n?4.  Keywords: Vertex equitable labeling; Vertex equitable graph.  © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  doi: http://dx.doi.org/10.3329/jsr.v6i1.15044 J. Sci. Res. 6 (1), 79-85 (2014)